1976
DOI: 10.1111/j.1399-0039.1976.tb01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Histocompatibility (HL‐A) Antigens and Primary Open‐Angle Glaucoma

Abstract: To assess the association between open‐angle glaucoma and HL‐A antigens, the frequencies of 25 HL‐A antigens were determined in 49 patients with OAG and 22 patients with increased intraocular pressure, due to causes other than OAG, using the microcytotoxicity method. The results were compared to 250 individuals from the general population who were tested in the same laboratory at the same period of time. Using rigid statistical analysis, the incidence of the Bw35 antigen was found to be significantly (≪0.012) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…However, Francois proposed that children of glaucoma patients should all be moderate responders if this were correct, but only 29 out of 87 tested exhibited a response (Francois, 1977). Subsequent studies found an association between POAG and the histocompatibility loci HLA-A and HLA-B (Aviner et al, 1976; Bigger et al, 1972; Bigger et al, 1975), and between high response to steroids (> 31 mm Hg) and HLA-B12 (Becker et al, 1977; Becker et al, 1976). However, several other studies could not confirm the POAG findings (Damgaard-Jensen and Kissmeyer-Nielsen, 1978; Mayr and Grabner, 1978; Ritch et al, 1978).…”
Section: Clinical History and Geneticsmentioning
confidence: 99%
“…However, Francois proposed that children of glaucoma patients should all be moderate responders if this were correct, but only 29 out of 87 tested exhibited a response (Francois, 1977). Subsequent studies found an association between POAG and the histocompatibility loci HLA-A and HLA-B (Aviner et al, 1976; Bigger et al, 1972; Bigger et al, 1975), and between high response to steroids (> 31 mm Hg) and HLA-B12 (Becker et al, 1977; Becker et al, 1976). However, several other studies could not confirm the POAG findings (Damgaard-Jensen and Kissmeyer-Nielsen, 1978; Mayr and Grabner, 1978; Ritch et al, 1978).…”
Section: Clinical History and Geneticsmentioning
confidence: 99%
“…In simplex glaucoma, Aviner et al (1976) found higher frequency of HLA Bw35. We also found a higher frequency (18% against 9% in the control group) but this difference was not significant, perhaps due to a smaller material.…”
Section: Discussionmentioning
confidence: 97%
“…Patients with open angle glaucoma are reported to have significantly more HLA-B7 and B12, and it has been suggested that occurrence of these antigens is an indicator of the development of visual field loss (Shin et al 1977). Aviner et al (1976) found that Bw35 was more frequent among patients with open angle glaucoma in a material from New York, 47% against 23% in a control series.…”
mentioning
confidence: 97%
“…They furthermore reported that those types were of prognostic value. Aviner et al (1976) found an increase in HLA-BW35, not in B7, and a decrease of B12 (P < 0.05, corrected P a. m. Grumet et al (1971) (P corr.) non-significant).…”
mentioning
confidence: 90%